Preparação, caracterização e aplicação de eletrodos de nanotubos de carbono na determinação de Cr(III), Cr(VI) e flavonoides - Nobrega, Camila Bortolato Gomes da (2013)
The objective of this work is the development of a carbon nanotubes past electrode (CNTs) as electrochemical sensors in the analysis of flavonoids, (+) catechin and rutin, and Cr (III) and Cr (VI) ions, by differential pulse voltammetry (DPV). The electrodes were prepared with 60% w/ w multiple walls CNTs with diameter of 20 to 40 nm and 40% w/w of mineral oil, nujol. The analytical curves for organic compounds (+) catechin and rutin were performed in phosphate buffer pH 6.0 while those for Cr (III) and Cr (VI) the electrolyte was a mixture of HCl and KCl 0.1 mol L-1 and tetrabutylammonium bromide 0.15 mmol L-1. The (+) catechin showed a limit of detection (DL) of 5.4 x 10-8 mol L-1 and rutin 9.37 x 10-8 mol L-1. The standard addition method was used to analyse the samples of tea species Camellia sinensis (black, white and green) and pomegranate fruit (bark, leaf and fruit). The total content of flavonoids was determined, since it was not possible separate the analytical signal of the two organic species. The values found with the addition of (+) catechin or rutin standard solutions are close to those reported in the literature and agree with those obtained from UV-vis technique. From analytical curve of the Cr (VI) ion was obtained a DL of 1.1 x10-9 mol L-1 and a recovery factor (Frec) of 98.1%. For Cr (III) none analytical signal was obtained in the conditions used in this work. However, for the mixture of Cr (III) and Cr (VI) the total chromium content was determined with a Frec of 100.4%, at low ions concentrations. The method was not able to specialty the different chromium ions species.